The Leadership of Revivalist Kiai: Kiai’s Leadership Behaviours in Pesantren Shuffah Hizbullah Al-Fattah Cileungsi Bogor - Asy'ari, Hasyim; Marsela, Ades; Pardini, Agung; Amelia, Firda (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This study is aimed at describing kiai’s leadership behaviors and identifying the educational system organized by Pesantren Shuffah Hizbullah Al-Fatah in Cileungsi Bogor. This is a qualitative study with three techniques of data collection that are observation, interview, and document study. The results of the study show that revivalist Kiai can be generally defined as a model of pesantren leadership which is not only to foster students’ personality but also to form the cadres of new Islamic generation who have the commitment to upholding Islamic values in daily life. The leadership conception of revivalist Kiai is in line with the role model implemented by Rasulullah SAW during his leadership in Madinah. The existence of Pesantren Shuffah Hizbullah Al-Fatah is the transformation of the pesantren model which has been developed for centuries on Java Island. The educational model in Shuffah Hizbullah Al-Fatah is a combination of formal, nonformal, and informal educational models that is community-based with the mosque as the central. This pesantren has a special characteristic that is successful in involving various components of Muslim communities to become the students.